2013
DOI: 10.1111/acv.12096
|View full text |Cite
|
Sign up to set email alerts
|

Agreenstrategy for shark attack mitigation off Recife, Brazil

Abstract: Shark attacks on humans have prompted the implementation of shark control programs aiming at reducing local populations of potentially aggressive species using mostly gillnets. However, shark meshing produces ecological disturbances by inflicting severe mortality not only to sharks but also to several harmless, frequently endangered taxa, including cetaceans, sirenians and chelonids. A different methodological approach to mitigate shark peril off Recife combines bottom longlining and drumlines with comparably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 20 publications
0
50
0
1
Order By: Relevance
“…Each set, five lines of 15 hooks were set for a 24‐h period. Individual longlines could not be considered independent sampling, due to their potential effect on each other during the survey (Hazin & Afonso, ). Unit effort was calculated as the number of fishing days multiplied by the number of hooks: hook days, D H .…”
Section: Methodsmentioning
confidence: 99%
“…Each set, five lines of 15 hooks were set for a 24‐h period. Individual longlines could not be considered independent sampling, due to their potential effect on each other during the survey (Hazin & Afonso, ). Unit effort was calculated as the number of fishing days multiplied by the number of hooks: hook days, D H .…”
Section: Methodsmentioning
confidence: 99%
“…Coastal communities often demand intervention to reduce the risk of further attacks, especially if an unusually high number of incidents have occurred in a short space of time (Curtis et al 2012). A wide range of mitigation measures to decrease the risks of shark attack have been implemented, including short-term targeted shark fishing, long-term deployment of shark-fishing devices such as gillnets or drumlines, use of shark repellents and, more recently, scientific studies to understand better the biology, ecology and behaviour of sharks (Cliff and Dudley 1992;Wetherbee et al 1994;Nel and Peschak 2006;Beschta and Ripple 2009;Cliff and Dudley 2011;O'Connell et al 2011O'Connell et al , 2014Hazin and Afonso 2014). In general, knowledge of apex shark predators remains scarce compared to their terrestrial counterparts (Beschta and Ripple 2009).…”
Section: Seasonal Variability Of Bull and Tiger Shark Presence On Thementioning
confidence: 99%
“…In the north-western Atlantic, Beerkircher et al (2008) reported that of the total combined catches of mobulids and dasyatids by the US pelagic longline fishery, 97% were released alive. A somewhat higher mortality in longlines was reported by Hazin and Afonso (2014) in north-eastern Brazil for devil rays (Mobula sp. ), but their sample size was small (n ¼ 6, 50% dead).…”
Section: By-catch Patternsmentioning
confidence: 66%